Gendered Customary Sanctions in the Same-Clan Marriage Prohibition: A Maslahah Mursalah Perspective from Kuantan Singingi - Alzekrillah Syaf; Adi Harmanto (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
This study examines the gender dimension of the prohibition against marriage within the same clan in the matrilineal community of Kuantan Singingi, Riau, a norm upheld across generations based on the principle of adat basandi syarak, syarak basandi Kitabullah, even though it is not explicitly prohibited by Islamic law. Unlike previous studies, which tended to be normative-anthropological and rarely distinguished prohibitions from their sanctions, this study highlights the gendered burden of these customary sanctions. By integrating Berger’s social construction theory and Schutz’s phenomenology to trace the formation of the norm, Bourdieu’s concept of symbolic violence to analyze its enforcement, and the principle of maslahah mursalah to evaluate its sanctions, this qualitative study of 30 informants (traditional leaders, religious scholars, KUA officials, and community members) across five subdistricts found that this norm is accepted as a preventive mechanism to maintain clarity of lineage and social harmony. However, its punitive sanctions fall under the category of maslahah mulghah because they cause disproportionate harm: permanent ostracism and stigma passed down to children, which structurally burdens women through their maternal roles within the clan, limited agency within male-dominated traditional institutions, and the stigma attached to their descendants, thereby creating layered injustice. This study recommends a shift toward restorative mechanisms based on iṣlāḥ: customary mediation, social education, symbolic sanctions, and the elimination of stigma against children.